2018
DOI: 10.1111/jfpp.13712
|View full text |Cite
|
Sign up to set email alerts
|

Combination of sea tangle powder and high-pressure treatment as an alternative to phosphate in emulsion-type sausage

Abstract: A series of experiments were conducted to determine the possibility of using sea tangle powder (STP) and/or its combination with high pressure (HP) as substitutes for phosphate in emulsion‐type sausages. The sausages with STP (1.5% and 3%) had similar cooking loss to sausages with 0.2% sodium pyrophosphate (PC), without a negative effect on overall acceptability, except for texture property, which was inferior to PC (p < 0.05). Instrumental texture properties of sausages containing 3% STP were improved by HP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A similar finding has been observed by Lee et al . (2018), who used the HP treatment and sea tangle powder combinations to reduce the phosphate concentration in emulsion‐type sausage and found that the pH and protein solubility were increased after HP treatment. Poulter et al .…”
Section: Resultsmentioning
confidence: 99%
“…A similar finding has been observed by Lee et al . (2018), who used the HP treatment and sea tangle powder combinations to reduce the phosphate concentration in emulsion‐type sausage and found that the pH and protein solubility were increased after HP treatment. Poulter et al .…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of algae, as a non-traditional ingredient with strong and specific flavor, may adversely affect the sensory attributes of reformulated products, as the traditional formulation’s ingredients play a crucial role in shaping the typical sensory characteristics preferred by consumers for each product. However, there were no significant differences in flavor and the juiciness of fresh pork sausages made with 3% Sea tangle, while the springiness, hardness, and overall sensory acceptability were improved by the addition of this macroalga [ 56 ]. Contrarily, the same seaweed in the same concentration, but this time used as an ingredient in fat-reduced pork patties [ 22 ] or in breakfast sausages [ 23 ], exhibited no significant difference in overall sensory acceptability compared to the control samples.…”
Section: Resultsmentioning
confidence: 99%
“…Sea tangle ( Lamina japonica ) is a type of brown algae with water retention and binding ability that has been added to totally replace the sodium pyrophosphate (0.2%) in an emulsion-type sausage. Both 1.5 and 3% of sea tangle offered similar cooking loss to sausages without negative effects on sensory acceptability [ 88 ]. Natural calcium powders obtained from eggs and oyster shells were used individually or in combination as phosphate alternatives to formulate pork meat products [ 94 ].…”
Section: Clean-label Ingredients In Meat Productsmentioning
confidence: 99%